Foundations of Qt Development - Thelinn, Johan (Apress, 2012)
My very first computer, a ZX81, did not have a graphical user interface. Compared with today’s offerings, I’d say it hardly had graphics at all. That computer never got me excited about programming, mostly because the manuals were in English and I didn’t yet know how to read the language. Then I met the ABC80, a Swedish computer from Luxor. It had the same Z80 processor, 16 kilobytes of RAM, and no real graphics to talk about. It did have an introduction to BASIC in Swedish, though, so it got me started with programming. My next computer experience was an Atari ST. I must admit that in the beginning I used it mostly for gaming. But as time passed I was thrilled about the possibilities of the Atari for programming. I wrote games, utilities, and painting applications. I also ran into something that I learned to like: an API for handling windows and drawing graphics. Moving on, I got a PC. I learned C and C++, as well as how to do 3D graphics in software (this was before 3D graphics cards). I was introduced to the Internet and learned lots of new things from newsgroups and FAQs. I also got my first paid job as a programmer, processing scientific data using FORTRAN.